One-Step Synthesis and Photoluminescence Evaluation of Cadmium-Containing Quantum Dots - Shukla, Nisha; Nigra, MichaelM.; Ondeck, Abigail D. (Nano-Micro Letters, 2012)
We have developed a simple one-step process for synthesis of ternary quantum dots (ZnCdSe, MgCdSe) with photoluminescence wavelengths ranging from the red to the blue region of the visible spectrum. The primary aim of this work was to develop a synthesis for the preparation of Cd-containing quantum dots using a Cd precursor with lower toxicity than those used in common syntheses. This synthesis makes use of Cd(acac)2 which is significantly less toxic than precursors such as CdO and CdCl2. We have studied the effect of solvent boiling point, precursors and reaction time on the photoluminescence properties of the ternary quantum dots. Ternary quantum dots synthesized from Cd(acac)2 in low boiling point solvents have photoluminescence wavelengths in the blue region, while those synthesized in high boiling point solvents have photoluminescence wavelengths in the red region.